4q25 Microdeletion with Axenfeld-Rieger Syndrome and Developmental Delay. (9th February 2023) - Kawanami, Yukino; Horinouchi, Tomoko; Morisada, Naoya; Kato, Takeshi; Nozu, Kandai
Abstract : We encountered a case with congenital iris coloboma, omphalocele, and developmental delay with a 2.5 Mb deletion on chromosome 4q25 encompassing PITX2, leading to Axenfeld-Rieger syndrome (ARS), NEUROG2, and ANK2 . ARS is characterized by the aplasia of the anterior eye, odontogenesis, and abdominal wall aplasia. In our case, iris coloboma and omphalocele were thought to be caused by PITX2 haploinsufficiency. However, these symptoms are nonspecific, and clinical symptoms alone can make it difficult to make a correct diagnosis. In addition, the genes responsible for developmental delay, among others, are not well understood. Developmental delay, in this case, might be caused due to NEUROG2 haploinsufficiency. In spite of the partial deletion of ANK2, the causative gene of long QT syndrome type 4, the electrocardiogram was normal. Genetic testing can lead to a correct diagnosis, and it may be effective in detecting complications.